(untitled) - Hammond, John H. (Bristol, 1981)
Contents: The camera obscura effect - the formation of an image by light passing through a small hole into a darkened room or box - has been known for many centuries. It was probably first noted by Chinese philosophers, and the instrument was later developed by European astronomers for observing sunspots and planetary movements, as well as by magicians and showmen as an entertaining diversion
Keywords: Camera,Máy chụp ảnh; History,Lịch sử